2018
DOI: 10.1007/s11356-018-2888-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and ecotoxicological risk assessment of 49 elements in sludge from wastewater treatment plants of Chongqing and Xiamen cities, China

Abstract: Limited information about the sludge quality is a major constraint for its usage and proper disposal. This study investigated the occurrence of 49 elements in sludge from 11 wastewater treatment plants (WWTPs) in Chongqing and Xiamen cities of China. The concentration of 46-detected elements ranged from 16.2 μg kg (Pt) to 55.0 g kg (Al) on dry solid basis in the sludge. The enrichment factor of most of the elements was > 1.5, indicating their possible anthropogenic origin. The precious metals had considerably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This could be explained by the fact that the highest Cf was characteristic for those heavy metals of relatively low toxicity (Zn), and soil SS and SSCh application did not induce any changes in the concentrations of highly toxic Cd and Pb. Comparison of 11 sewage sludges from wastewater treatments plants revealed that highest PERI values were characteristic for those SS with highest Cd, Pb, and As concentrations [26]. Nevertheless, PERI indices increased with SS and SSCh dose (rSS = 0.98, rSSCh = 0.92, p < 0.05), indicating that long-term soil amendment with high SS or SSCh doses might pose ecological risk.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This could be explained by the fact that the highest Cf was characteristic for those heavy metals of relatively low toxicity (Zn), and soil SS and SSCh application did not induce any changes in the concentrations of highly toxic Cd and Pb. Comparison of 11 sewage sludges from wastewater treatments plants revealed that highest PERI values were characteristic for those SS with highest Cd, Pb, and As concentrations [26]. Nevertheless, PERI indices increased with SS and SSCh dose (rSS = 0.98, rSSCh = 0.92, p < 0.05), indicating that long-term soil amendment with high SS or SSCh doses might pose ecological risk.…”
Section: Resultsmentioning
confidence: 96%
“…The soil contamination levels were classified as follows: low degree-C f < 1, moderate degree-1 < C f < 3, high degree-3 < C f < 6, and very high degree-C f ≥ 6 [26].…”
Section: Experimental Designmentioning
confidence: 99%
“…Generally, multivariate statistical and exploratory data analysis techniques are considered for explaining the spatial or temporal variations . In this context, cluster analysis (CA), principal component analysis (PCA), and discriminant analysis (DA) are widely used multivariate statistical tools for surface water quality and risk assessment. ,,, These methods rely on reducing the data dimensionality to highlight temporal and spatial variations based on limited uncorrelated variables. , However, these methods do not explain the relative contribution of individual spatial sites in variability and their influences on respective neighboring sites. In general, the geographical phenomena are considered continuous, but the discretized quantities are usually alike in closer proximities .…”
Section: Introductionmentioning
confidence: 99%